2022
DOI: 10.3390/diagnostics12020515
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Viral RNA Is Detected in the Bone Marrow in Post-Mortem Samples Using RT-LAMP

Abstract: Since the emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in late 2019, viral RNA has been detected in several different human tissues and organs. This study reports the detection of SARS-CoV-2 RNA in the bone marrow. Post-mortem samples were taken in a sterile manner during two forensic autopsies from the nasopharyngeal region, vitreous humor, cerebrospinal fluid, and bone marrow. SARS-CoV-2 was subsequently diagnosed via Genomtec® SARS-CoV-2 EvaGreen® RT-LAMP CE-IVD Duo Kit. In both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…The maximum PMI range was 6 days. Another study [ 21 ] detected viral RNA in the bone marrow (2/2, 100%) at 12 days postmortem using the real-time loop-mediated isothermal amplification (RT-LAMP) method and confirmed with agarose gel electrophoresis. At skin level, a study of deceased bodies of COVID-19 decedents reported the RNA persisted in swab specimens of hands (14/24, 58.3%), wrists (14/24, 58.3%), shoulders and hips (13/24, 54.16%), and body bag surface (6/24, 25%) with PMI of 0–17 days [ 35 ].…”
Section: Resultsmentioning
confidence: 97%
“…The maximum PMI range was 6 days. Another study [ 21 ] detected viral RNA in the bone marrow (2/2, 100%) at 12 days postmortem using the real-time loop-mediated isothermal amplification (RT-LAMP) method and confirmed with agarose gel electrophoresis. At skin level, a study of deceased bodies of COVID-19 decedents reported the RNA persisted in swab specimens of hands (14/24, 58.3%), wrists (14/24, 58.3%), shoulders and hips (13/24, 54.16%), and body bag surface (6/24, 25%) with PMI of 0–17 days [ 35 ].…”
Section: Resultsmentioning
confidence: 97%
“…The hyper-activation of T cells is a well-studied mechanism in chronic viral infections ( 108 ) and is often dependent on the levels of viral persistence in the circulation. The reason for the prolonged activation of T cells in COVID-19 could be owing to the persistence of viral antigens in the bone marrow, that indirectly affect the circulating lymphocytes ( 109 ). In addition, this may also be attributed to an ongoing chronic inflammation resulting from fibrosis/on-going tissue repair in the lung of patients recovering from COVID-19 ( 110 , 111 ).…”
Section: Discussionmentioning
confidence: 99%
“…The hyper-activation of T cells is a well-studied mechanism in chronic viral infections [98] and is often dependent on the levels of viral persistence in the circulation. The reason for the prolonged activation of T cells in COVID-19 could be owing to the persistence of viral antigens in the bone marrow, that indirectly affect the circulating lymphocytes [99]. In addition, this may also be attributed to an ongoing chronic inflammation resulting from fibrosis/on-going tissue repair in the lung of patients’ recovering from COVID-19 [100, 101].…”
Section: Discussionmentioning
confidence: 99%